PENGARUH RELGIUSITAS, TEKANAN, KESEMPATAN DAN RASIONALISASI TERHADAP TINDAKAN KECURANGAN (Studi pada Aparatur Sipil Negara di Sekretariat Daerah Kabupaten Semarang) - Putri Ayu Noviyanti; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2023)
Fraud is an intentional act that is consciously carried out to gain profit. Fraud can result in both material and non-material losses to the organization. Therefore, organizations need to know the causes of employees committing fraud so that preventive measures can be taken to minimize these actions. The purpose of this research is to examine the causes of fraudulent acts using the viewpoints of religiosity, pressure, opportunity, and rationalization. The sample used in this study was 103 respondents from the State Civil Apparatus who worked at the Regional Secretariat of Semarang Regency. The data used are primary data with data collection methods, namely direct distribution of questionnaires as measured by a Likert scale. Hypothesis testing was carried out using multiple linear regression analysis using IBM SPSS version 26 software. The results of this study indicate that religiosity, pressure, and rationalization have a positive and significant effect on fraudulent acts, but opportunity does not influence fraudulent acts.